Detection of nitrite and nitrate ions in water by graphene oxide as a potential fluorescence sensor - Ing, Hua Tang (2015)
In this study, graphene oxide (GO) was used as a new fluorescence sensor for detection of nitrite (NO2 -) and nitrate (NO3 -) ions. The GO was synthesized via an improved Hummers' method, and the properties of GO were examined by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscope (TEM). The XRD pattern showed the presence of (002) plane at 2? of 9.5o while the FTIR spectrum showed the presence of C-OH, C=O, C=C, C-O chemical bonds in the GO. The layer structure of the GO was confirmed from the TEM image. The sensing performance of the GO for NO2 - and NO3 - was evaluated by monitoring the emission sites of the GO at 567 nm, which was corresponded to the oxygen functional groups. Fluorescence quenching was observed, suggesting that the GO interacted well with both NO2 - and NO3 - ions. The linear Stern-Volmer plots were obtained in the concentration range of 1-10 mM, indicating the potential ability of the GO as the fluorescence sensor. The quenching constants for the detections of NO2 - and NO3 - were 4.8 10-2 and 1.2 10-2 mM-1, respectively, suggesting that the GO has greater sensitivity towards the NO2 - than the NO3 - ion.